Fine tuning bacterial chemotaxis: analysis of Rhodobacter sphaeroides behaviour under aerobic and anaerobic conditions by mutation of the major chemotaxis operons and cheY genes. - Shah, D; Porter, S; Martin, A; Hamblin, P; Armitage, J (2000)
Rhodobacter sphaeroides chemotaxis is significantly more complex than that of enteric bacteria. Rhodobacter sphaeroides has multiple copies of chemotaxis genes (two cheA, one cheB, two cheR, three cheW, five cheY but no cheZ), controlling a single 'stop-start' flagellum. The growth environment controls the level of expression of different groups of genes. Tethered cell analysis of mutants suggests that CheY(4) and CheY(5) are the motor-binding response regulators. The histidine protein kinase CheA(2) mediates an attractant ('normal') response via CheY(4), while CheA(1) and CheY(5) appear to mediate a repellent ('inverted') response. CheY(3) facilitates signal termination, possibly acting as a phosphate sink, although CheY(1) and CheY(2) can substitute. The normal and inverted responses may be initiated by separate sets of chemoreceptors with their relative strength dependent on growth conditions. Rhodobacter sphaeroides may use antagonistic responses through two chemosensory pathways, expressed at different levels in different environments, to maintain their position in a currently optimum environment. Complex chemotaxis systems are increasingly being identified and the strategy adopted by R.sphaeroides may be common in the bacterial kingdom.